1985
DOI: 10.1128/iai.49.3.670-673.1985
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation and stimulation of chemotaxis by Chlamydia trachomatis

Abstract: The stimulus for the migration of polymorphonuclear leukocytes (PMNs) in acute chlamydial infection was studied in vitro by examining the chemotaxigenic effect of L2 and DE Chlamydia trachomatis elementary bodies (EB) upon the plasma of three healthy donors. In each individual experiment, chemotactic response was assessed with PMNs and plasma from the same respective donor, and no specific antibodies against C. trachomatis were detected in the plasma of any donor. Chemotaxis was observed in an agarose plate as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Thus, the primary stimulus for the initiation of the acute inflammatory response should be the organism itself. Chlamydial EBs bind C3 and thereby initiate the alternative complement pathway (14); the binding site was found to be the chlamydial major outer membrane protein. However, a role for chlamydial lipopolysaccharide (LPS) in the initiation of the alternative pathway cannot be ruled out, especially since LPS is expressed in large amounts on the surfaces of infected cells early in the infection cycle (10,22).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the primary stimulus for the initiation of the acute inflammatory response should be the organism itself. Chlamydial EBs bind C3 and thereby initiate the alternative complement pathway (14); the binding site was found to be the chlamydial major outer membrane protein. However, a role for chlamydial lipopolysaccharide (LPS) in the initiation of the alternative pathway cannot be ruled out, especially since LPS is expressed in large amounts on the surfaces of infected cells early in the infection cycle (10,22).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies revealed that the early release of chlamydial antigens from the inclusion could be increased by the lipophilic microbicide compound C31G, presumably due to destabilization of the chlamydial inclusion membrane as well as direct removal of LPS from the chlamydial envelope (30). The early release of chlamydial LPS, which fixes complement by both the classical and alternative pathways to generate the potent chemoattractant C5a (10), likely serves as one of the first signals for the marked influx of polymorphonuclear leukocytes, observed in patients with cervicitis and endometritis (14). Further, in the case of LPS, it has been postulated that the altered fluidity of the plasma membrane of the infected epithelial cells may thwart destruction by cytotoxic T cells (27).…”
mentioning
confidence: 99%
“…Several studies have shown that chlamydiae can activate the complement cascade in fresh serum in vitro (16) and that complement greatly enhances the neutralization of infectiv-* Corresponding author. ity by antibody (13,17).…”
mentioning
confidence: 99%